ВІДПОВІДАЛЬНІСТЬ УРЯДУ ЯК ЕЛЕМЕНТ ЙОГО КОНСТИТУЦІЙНО-ПРАВОВОГО СТАТУСУ - Дахова, І. І. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2016)
The article examines the constitutional and political responsibility; the content, the basis of government responsibility; tendencies of the constitutional and legal procedures regulating the expression of no confidence to the government.